Gorlin-Goltz syndrome associated with bilateral cleft lip and palate - Noemí Lorena Leiva Villagra; Sebastián Alejandro Véliz Méndez; Leonardo Esteban González Escobar; Carolina Andrea Salazar Ponce (Editorial Ciencias Médicas, 2015)
Introduction: Gorlin Goltz Syndrome (GGS) is an autosomal dominant inherited disorder. One of the minor criteria for such syndrome is the cleft lip and palate (CL/CP). The CL/CP is the most prevalent maxilofacial congenital anomaly, where a variable percent is associated with syndromes. Objective: To introduce the case of a patient with Gorlin Goltz Syndrome and associated bilateral cleft lip and palate. Main aspects of the Case: 12 years old patient, with diagnosis of GGS made for a geneticist. Characterized by the presence of cutaneous, osseous, dental, neurological anomalies, tumors, pits, mandibular prognathism and operated bilateral cleft lip palate. Principal Comments: It's important to recognize not only the characteristics associated with craniofacial area, but also with other parts of the body. The cleft lip and palate specialist must be part of the multidisciplinary team's relevant performance, since the most publications are approached to the surgical management of cysts and leave aside associated effects, as cleft lip and palate.